Introduction to tourism - Leuterio, Florida C. (Manila, Philippines : Rex Book Store, 2007)
The purpose of introduction to tourism is to provide students of tourism and practitioners with clear explanation of the concepts, elements, and practice of tourism as a discipline and as an industry.
Chapter 1. The Nature of tourism : Meaning and elements of tourism -- Chapter 2. Historical development of tourism : Tourism through the ages -- Chapter 3. Tourism services : The Lodging and food service industries -- Chapter 4. Historic sites, attractions, recreation, entertainment : preservation of cultural heritage -- Chapter 5. The role of travel agency : tourism channel of distribution -- Chapter 6. Introduction to meetings, conventions, and expositions : history of meetings, conventions, and expositions -- Chapter 7. Players in the convention and meetings industry : participants in conventions and meetings -- Chapter 8. International organizations in tourism : cooperation in tourism.
Includes bibliographical references and index.
Keywords: TOURISM -- STUDY AND TEACHING